2022
DOI: 10.1029/2021jb023060
|View full text |Cite
|
Sign up to set email alerts
|

The Rise, Peak and Decline of the Seismic Hazard Related to Hydraulic Fracturing Activities in the Duvernay Play, Fox Creek Area, Alberta

Abstract: We analyze the temporal evolution of the induced seismicity related to hydraulic fracturing activities in the Duvernay Formation, near Fox Creek, Alberta, Canada. For this analysis, we estimate annual Gutenberg‐Richter parameters, a(t) $a(t)$‐ and b(t) $b(t)$‐ values, and then calculate the annual likelihood of earthquakes greater than magnitude M>4 $M > 4$ from 2014 to 2020. The seismic hazard near Fox Creek has consistently decreased since 2015, from a 95% probability of an earthquake greater than magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…S16 in Supporting Information S1). More details about the causes behind the seismic hazard decline in the Fox Creek area between 2016 and 2020 can be found in Reyes Canales et al (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S16 in Supporting Information S1). More details about the causes behind the seismic hazard decline in the Fox Creek area between 2016 and 2020 can be found in Reyes Canales et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additional background can be found in the analysis conducted by Reyes Canales et al. (2022). Red Deer (Duvernay Formation): Induced events related to hydraulic fracturing activities at the East Duvernay Shale Basin have been recorded near the city of Red Deer (Wang et al., 2020).…”
Section: Natural and Induced Seismic Sources In Albertamentioning
confidence: 99%
“…In the Fox Creek area in central Alberta, Reyes-Canales et al 43 performed an assessment of event rates and Gutenberg-Richter b -values. This area is the subject of the Alberta Energy Regulator’s Subsurface Order No.…”
Section: Discussionmentioning
confidence: 99%
“…7 a). Reyes-Canales et al 43 suggested that some of this reduction in seismicity could be attributed to the targeting areas less susceptible to induced seismicity. However, it is also clear that there has been a reduction in the seismic activity of the eastern region inside the Fox Creek area that previously exhibited higher seismic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The process of water injection during oil and gas or geothermal energy development has been identified as a potential trigger for seismic activity, as it can lubricate faults, thereby reactivating them and inducing earthquakes (Dou et al, 2020a;Dou et al, 2020b;Shang et al, 2020). Statistics show a notable surge in earthquake frequency across the central and eastern United States following the intensification of shale gas development (van der Baan and Calixto, 2017;Canales et al, 2022). In regions and during periods with a lot of shale gas development activities, the frequency of earthquakes is significantly higher than that of other regions.…”
Section: ): Cacomentioning
confidence: 99%